Chemical Speciation, Risk Assessment and Pollution Level of Lead Metals in Road Dust of some Industry Zones and Urban Areas in Northern Vietnam - Thuy, Nguyen Thi Thu; Xuan, Vuong Truong; Le, Nguyen Thieu; Minh, Tu Binh (VNU Journal of Science: Natural Sciences and Technology; Vol 38 No 1, 2022)
This study analyzed the chemical speciation of Pb metal in road dust samples from six provinces in northern Vietnam. Samples were extracted according to Tesser's sequential extraction procedure [22] and measured by the ICP/MS method, with the total recovery of Pb ranged from 90.9% to 107%. The analysis results showed that Pb existed mainly in the form of residual fraction F5 (38.6%) > organic fraction (29.0%), > Fe/Mn oxide fraction (19.2%) > exchange fraction, and carbonate fraction (5.00% and 8.32%, respectively). The pollution indices such as geological accumulation index (I geo ), individual contamination factor (ICF),  and risk assessment index (RAC%) were utilized to evaluate pollution levels. The values of I geo of Pb in samples ranged from 1.80 to 2.65, with a mean value of 2.24. The value of ICF varied from 0.60 to 2.87, with a mean value of 2.04. The values of RAC ranged from 4.47% to 23.2%, with a mean value of 13.3%. In general, the concentration of Pb in most of the studied samples in the six provinces were classified as low pollution and risk levels according to Igeo, ICF and RAC. However, in some provinces which have many industries producing electronic components, steel ore, and densely populated urban areas, the pollution level of Pb was from moderate to large, potentially affecting the environment of the studied areas.